Mathematical modelling of unisothermal moisture transfer and deformation-relaxation fields in capillary-porous materials with fractal structure - Sokolowskyi, Yaroslav; Shymanskyi, Volodymyr (Видавництво Львівської політехніки, 2013)
We have considered the mathematical model of the distribution of deformation-relaxation and heat-mass fields in capillary-porous materials with fractal structure. We used differential equations in partial derivatives of fractional order to describe it. Difference method obtained the numerical solution of the problem for different values of the fractional derivative.
Keywords: fractional order of a derivative; fractal; unisothermal moisture transfer; capillary-porous materials; numerical method; deformation-relaxation field